2012
DOI: 10.1080/09540121.2012.701717
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sexual activity and risk behaviors among PLWHA initiating ART in rural district hospitals in Cameroon – Data from the STRATALL ANRS 12110/ESTHER trial

Abstract: The continued scaling-up of antiretroviral therapy (ART) in Sub-Saharan Africa provides an opportunity to further study its impact on sexual behaviors among people living with HIV/AIDS (PLWHA). We explored time trend and correlates of sexual activity among PLWHA initiating ART in Cameroon and compared sexual risk behaviors between patients sexually active before and after initiating ART and those resuming sexual activity after ART initiation. Analyses were based on longitudinal data collected within the random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In a study in Atlanta, USA, results show that nonadherent Men who have Sex with Men (MSM) were more likely to have a greater number of sex partners and engage in unprotected sex than those who were adherent [7]. Also, there is evidence that ART reinvigorates sexual desires and sexual activity of PLHIV; and that few PLHIV practice safe sex [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Atlanta, USA, results show that nonadherent Men who have Sex with Men (MSM) were more likely to have a greater number of sex partners and engage in unprotected sex than those who were adherent [7]. Also, there is evidence that ART reinvigorates sexual desires and sexual activity of PLHIV; and that few PLHIV practice safe sex [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown nevertheless by several studies that initiating ART may have dual impact on risky behaviors: Higher unsafe sex among PLWHA on ART and several studies from Africa have found an increase in high risk sexual behavior among persons initiating ART [23][24][25]. On the other hand, ART initiation has lowered the risk behaviors among PLWHA [12,16,19,22,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…WHO reported that more than 14.9 million of people living with HIV were under antiretroviral therapy worldwide, including 13.5 million (more than 90%) in low-and middle-income countries and this was only 40% of people living with HIV [7]. In the other hand, the availability of therapeutic protocols in Africa remains the lowest meanwhile this part of the world shelters more than 90% of the ART (Antiretroviral treatment) needs [8,9]. Like many countries, Cameroon adopted this system as one of the strategic axes of its national policy to control HIV through the creation and extension of care units since access to ART was made free in 2007 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, as in many sub-Saharan countries, the prevalence of HIV is still high (4.3% in 2011) as the number of new infections keep increasing (6 new infections per hour) [15,16]. Sexual activity remains as important as the fertility index among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation